On the robustness of brain gain estimates - Michel Beine; Frédéric Docquier; Hillel Rapoport (Bar-Ilan University, Department of Economics, 2009)
Recent theoretical studies suggest that migration prospects can raise the expected return to human capital and thus foster education investment at home or, in other words, induce a brain gain. In a recent paper (Beine, Docquier and Rapoport, Economic Journal, 2008) we used the Docquier and Marfouk (2006) data set on emigration rates by education level to examine the impact of brain drain migration on gross (pre-migration) human capital formation in developing countries. We found a positive effect of skilled migration prospects on human capital growth in a cross-section of 127 developing countries, with an elasticity of about 5 percent. In this paper we assess the robustness of our results to the use of alternative brain drain measures, definitions of human capital, and functional forms. We find that the results hold using the Beine et al. (2007) alternative brain drain measures controlling for whether migrants acquired their skills in the home or in the host country. We also regress other indicators of human capital investment on skilled migration rates and find a positive effect on youth literacy while the effect on school enrolment depends on the exact specification chosen
Keywords: 330; Brain Drain; Internationale Wanderung; Humankapital; Bildungsinvestition; Messung; Entwicklungsländer